Bioactive Antimicrobial Peptides: A New Weapon to Counteract Zoonosis - Luisa Zupin; Carlos André dos Santos-Silva; Aya R. Hamad Al Mughrbi; Livia Maria Batista Vilela; Ana Maria Benko-Iseppon; Sergio Crovella (Microorganisms, 2022)
Zoonoses have recently become the center of attention of the general population and scientific community. Notably, more than 30 new human pathogens have been identified in the last 30 years, 75% of which can be classified as zoonosis. The complete eradication of such types of infections is far out of reach, considering the limited understanding of animal determinants in zoonoses and their causes of emergence. Therefore, efforts must be doubled in examining the spread, persistence, and pathogenicity of zoonosis and studying possible clinical interventions and antimicrobial drug development. The search for antimicrobial bioactive compounds has assumed great emphasis, considering the emergence of multi-drug-resistant microorganisms. Among the biomolecules of emerging scientific interest are antimicrobial peptides (AMPs), potent biomolecules that can potentially act as important weapons against infectious diseases. Moreover, synthetic AMPs are easily tailored (bioinformatically) to target specific features of the pathogens to hijack, inducing no or very low resistance. Although very promising, previous studies on SAMPs’ efficacy are still at their early stages. Indeed, further studies and better characterization on their mechanism of action with in vitro and in vivo assays are needed so as to proceed to their clinical application on human beings.